Association between socioeconomic status and the development of mental and physical health conditions in adulthood: a multi-cohort study. (March 2020) - Kivimäki, Mika; Batty, G David; Pentti, Jaana; Shipley, Martin J; Sipilä, Pyry N; Nyberg, Solja T; Suominen, Sakari B; Oksanen, Tuula; Stenholm, Sari; Virtanen, Marianna; Marmot, Michael G; Singh-Manoux, Archana; et al.
Summary: Background: Socioeconomic disadvantage is a risk factor for many diseases. We characterised cascades of these conditions by using a data-driven approach to examine the association between socioeconomic status and temporal sequences in the development of 56 common diseases and health conditions. Methods: In this multi-cohort study, we used data from two Finnish prospective cohort studies: the Health and Social Support study and the Finnish Public Sector study. Our pooled prospective primary analysis data comprised 109 246 Finnish adults aged 17–77 years at study entry. We captured socioeconomic status using area deprivation and education at baseline (1998–2013). Participants were followed up for health conditions diagnosed according to the WHO International Classification of Diseases until 2016 using linkage to national health records. We tested the generalisability of our findings with an independent UK cohort study—the Whitehall II study (9838 people, baseline in 1997, follow-up to 2017)—using a further socioeconomic status indicator, occupational position. Findings: During 1 110 831 person-years at risk, we recorded 245 573 hospitalisations in the Finnish cohorts; the corresponding numbers in the UK study were 60 946 hospitalisations in 186 572 person-years. Across the three socioeconomic position indicators and after adjustment for lifestyle factors, compared with more advantaged groups, low socioeconomic status was associated with increased risk for 18 (32·1%) of the 56 conditions. 16 diseases formed a cascade of inter-related health conditions with a hazard ratio greater than 5. This sequence began with psychiatric disorders, substance abuse, and self-harm, which were associated with later liver and renal diseases, ischaemic heart disease, cerebral infarction, chronic obstructive bronchitis, lung cancer, and dementia. Interpretation: Our findings highlight the importance of mental health and behavioural problems in setting in motion the development of a range of socioeconomically patterned physical illnesses. Policy and health-care practice addressing psychological health issues in social context and early in the life course could be effective strategies for reducing health inequalities. Funding: UK Medical Research Council, US National Institute on Aging, NordForsk, British Heart Foundation, Academy of Finland, and Helsinki Institute of Life Science.